2014
DOI: 10.1371/journal.pone.0094295
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Patterns and Health Care Seeking Behavior among Older Widows in India

Abstract: In the process of health transition, India is facing rapid pace of demographic aging. Rapid increase in older adult population posed serious concerns regarding health and health care utilization for them. However, very limited research documented resultant implications of demographic aging for health and health care use in the nexus of marital status and gender. With this perspective, the present study examined patterns in morbidity prevalence and health seeking behaviour among older widows in India. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 28 publications
1
58
2
Order By: Relevance
“…Agrawal and Keshri () revealed that the prevalence of communicable diseases was lower among older widows compared with older widowers. Perkins et al () found that a widower who had impaired cognitive ability and a mental disorder experienced poorer health.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Agrawal and Keshri () revealed that the prevalence of communicable diseases was lower among older widows compared with older widowers. Perkins et al () found that a widower who had impaired cognitive ability and a mental disorder experienced poorer health.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies revealed that the older widows and widowers managed their emotional pain and suffering thanks to support described as social bonds, family support or support from friends and that their health problems made daily life a struggle (Agrawal & Keshri, 2014;DiGiacomo et al, 2013;Ghesquiere et al, 2013;Jeon et al, 2013;Perkins et al, 2016;Tiedt et al, 2016;Xu et al, 2017;Zhou & Hearst, 2016). In four studies, the participants needed support from their children and families (Jeon et al, 2013;Panagiotopoulos et al, 2013;Tiedt et al, 2016;Xu et al, 2017), as well as from other people (DiGiacomo et al,2013;Ghesquiere et al, 2013).…”
Section: Emotional Challenges Related To Experiences Of Bereavementmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Agrawal et al examined patterns in morbidity prevalence and found that morbidity prevalence was 13% greater among older widows compared to older widowers. 14 Adjusted prevalence of communicable and noncommunicable diseases was found 74 and 192 per 1000 older widows respectively.…”
mentioning
confidence: 97%